Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Hasil Keterampilan Berbicara Siswa Kelas IV SD Inpres Tompasobaru 1 - Putry Patricia Mandolang; Richard D.H. Pangkey; Jennej J. Rawung (Peneliti.net, 2023)
This study aims to improve speaking learning outcomes through the application of the role-playing learning model for fourth-grade students of SD Inpres Tompasobaru 1. The method used in this research is the Class Action Research Approach (CAR), using the spiral model from Kemmis and Mc Taggart (Aqib Zainal, 2006:31) with four stages: (1) Planning, (2) Action, (3) Observation, (4) Reflection. The subjects of this study were fourth-grade students of SD Inpres Tompasobaru 1. The data collection technique used in this study was observation technique (observation and test). While the data obtained will be analyzed by calculating the proportion and average student learning outcomes. The results showed that the learning outcomes campaign in the first cycle was 69%, in the second cycle it increased to 85%. Thus, the role-playing learning model can improve the learning outcomes of speaking class IV SD Inpres Tompasobaru 1.